2017
DOI: 10.3892/ol.2017.6313
|View full text |Cite
|
Sign up to set email alerts
|

WNT1-inducible signaling pathway protein-1 contributes to tumor progression and treatment failure in oral squamous cell carcinoma

Abstract: Abstract. WNT1-inducible-signaling pathway protein-1 (WISP-1) belongs to the family of cysteine rich 61/connective tissue growth factor/nephroblastoma overexpressed matricellular proteins, which are involved in various biological processes, including cell adhesion, proliferation, differentiation, angiogenesis and carcinogenesis. In the present study, the expression of WISP-1 was investigated, and its association with clinicopathological factors and prognosis in patients with oral squamous cell carcinoma (OSCC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Previous research has highlighted the importance of the role played by WISP-1 and WISP-1 polymorphisms in OSCC [50][51][52]. For instance, not only does WISP-1 increase tumor cell invasion and inhibit apoptosis in the human OSCC SCC-1483 cell line [50], but also, certain WISP-1 single-nucleotide polymorphisms increase the susceptibility to OSCC and these associations are compounded by smoking and betel quid chewing [51]. Moreover, researchers have reported finding that WISP-1 hypomethylation is associated with lymph node metastasis in patients with OSCC [52].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has highlighted the importance of the role played by WISP-1 and WISP-1 polymorphisms in OSCC [50][51][52]. For instance, not only does WISP-1 increase tumor cell invasion and inhibit apoptosis in the human OSCC SCC-1483 cell line [50], but also, certain WISP-1 single-nucleotide polymorphisms increase the susceptibility to OSCC and these associations are compounded by smoking and betel quid chewing [51]. Moreover, researchers have reported finding that WISP-1 hypomethylation is associated with lymph node metastasis in patients with OSCC [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression and function of WISP1 in various tumors are reported differently. Some studies have reported that WISP1 is highly expressed in some tumors and functions as an oncogene . However, other studies have also demonstrated that WISP1 has low expression in tumor and plays the role of a tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has also demonstrated that Tp53 mutation may promote WISP1 expression in mouse PDAC cells ( Wang et al, 2015 ). Recent studies had shown that WISP1 acts as a new oncogene in glioblastoma ( Jing et al, 2017 ), oral squamous cell carcinoma ( Jung et al, 2017 ), gastric cancer ( Jia et al, 2017 ), melanoma ( Shao et al, 2016 ), and colon cancer ( Wu et al, 2016 ). Also, Yang et al (2015) showed that patients with high expression of WISP-1 had a shorter survival time independent of clinical stage and lymphatic metastasis status in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%